Nietzsche-Wagner: a cross of Swords - Quijano Restrepo, Luis Guillermo (Disertaciones, 2017)
The object of the present essay is to show the importance of Richard Wagner as person and artist in Nietzsche’s philosophy, in concordance with the fundamental problem in his work : the tragedy and de concept of the Dionysian in itself, as an element primordially musical and agent of reality’s transfiguration.
Keywords: Richard Wagner; Nietzsche; Apollonian; Dionysian; Drama; Tragedy